SIFAT PENGKARATAN LIMA JENIS KAYU ASAL CIAMIS TERHADAP BESI - Djarwanto (Jurnal Penelitian Hasil Hutan, 2013)
Five wood species namely tangkalak (Litsea roxburghii Hassk.), cangkring (Erythrina fusca Lour.), kayu putih Melaleuca cajuputi Powell.), ki tanab (Zanthoxylen rhetsa DC.), and huru leneur (Sterculia cordata Blume), were evaluated based on their metal corrosion properties using jam-pot methods. Wood samples were extracted from two tree stands, divided radially into three groups, namely outer, middle and inner part of log. The results showed that iron corrosion was found in all wood species. The corrosion intensities were identified by the weight loss of the attached metal screws. Higher corrosion rates were found on samples of kayu putih. The highest weight loss of screw was found on kayu putih samples extracted from midle part (B part) of P-II tree, i.e. 2.76%. The lowest weight loss of screw was encountered on tangkalak wood samples extracted from inner part (C. part) of P-Il tree. The percentage of samples weight loss on tree-1 was lower (0.55%) than that on tree-11 i.e. 0.72%. Comparing those two sample groups, the weight loss of outer part (A) and inner part (C) were lower than that of the middle part of logs.